Discovery and characterization of novel indole and 7-azaindole derivatives as inhibitors of β-amyloid-42 aggregation for the treatment of Alzheimer's disease. Issue 6 (15th March 2017) - Sreenivasachary, Nampally; Kroth, Heiko; Benderitter, Pascal; Hamel, Anne; Varisco, Yvan; Hickman, David T.; Froestl, Wolfgang; Pfeifer, Andrea; Muhs, Andreas
Graphical abstract: Abstract: The aggregation of amyloid-β peptides into cytotoxic oligomeric and fibrillary aggregates is believed to be one of the major pathological events in Alzheimer disease. Here we report the design and synthesis of a novel series of indole and 7-azaindole derivatives containing, nitrile, piperidine and N-methyl-piperidine substituents at the 3-position to prevent the pathological self-assembly of amyloid-β. We have further demonstrated that substitution of the azaindole and indole derivatives at the 3 positions is required to obtain compounds with improved physicochemical properties to allow brain penetration.